Comparative Study on (Dis)use of Heritage in Ouro Preto-Br and Oporto-Pt - Burkowski, Rodrigo (2017)
Appropriation arrangements of a particular territory expose the contradictions inherent in life in society. Those contradictions, in turn, do not depend on the existence of laws and regulations, setting up the materialization of different evolutionary processes. For this investigation, urban dynamics are influenced and compelled to respond to the particular pressures of capitalism, a late capitalism in the case of Ouro Preto, in which patrimonialization incurs break hegemonic models of space uses and reuses. The state apparatus appears plastering latent transformations and confirms the role of the ‘heritage-person’ as a potential heritage aggressor. This research’s main objective is to compare the dynamics of the heritage’s appropriation and use in Ouro Preto, Minas Gerais, Brazil and Oporto, Portugal. More specifically, it searches to understand the historical perspective of historic centre appropriation, its heritage value and its value for the tourism; to compare the heritage conservation legislation in both cities; and to study the problems of public equipment rehabilitation. This article presents the first step results of comparisons between the legislation on the urban rights (real estate assets) in Portugal and Brazil. It also presents the statistical comparison of types of infringement and their penalties applied by the historic centres rehabilitation programmes in Oporto and Ouro Preto. Through a systematic survey, the researchers diagnosed the main infringements committed to heritage assets. The use of records allowed to understand and to classify the types of offenses. These data for both cities will be compared, as well as each country’s or international guidelines regarding urban rehabilitation.